ANALISIS PENGARUH GAYA HIDUP, BRAND DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DI TOKO BOZE VAPE STORE KARTASURA - Shodikin, Rodzi; Rahmawan, Ginanjar (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2021)
Thisistudy aimsito determineithe effectiof lifestyle,ibrand brands and price perceptions on purchasingidecisions at Boze Vape Store Kartasura. Theipopulation ofithis study were all vape consumers in the Boze vape store, Kartasura. Theisample ofithis studyiamounted toi50 people. This research samplingitechnique using accidental sampling. The data analysis of this research used multiple linear regression analysis which was processed using the Statistical Package for Social Science (SPSS) program. The results showed that there was a significant influence between lifestyle and purchasing decisions, with a p value <0.05. There is a relationship between brand brands and purchasingidecisions, withia value of p <0.05. Thereiis aisignificant influenceibetween perceived price andipurchasing decisions,iwith a p value <0.05.